Weak association between subjective symptoms of and objective testing for dry eyes and dry mouth: results from a population based study. Issue 1 (1st January 1998) - Hay, Elaine M; Thomas, E; Pal, B; Hajeer, Ali; Chambers, H; Silman, A J
Abstract : OBJECTIVES: To determine associations between symptoms of dry eyes and dry mouth and objective evidence of lacrimal and salivary gland dysfunction in a population based sample. To determine associations between these elements and the presence of autoantibodies. METHODS: A cross sectional population based survey. Subjects were interviewed and examined (Schirmer-1 test and unstimulated salivary flow) for the presence of dry eyes and mouth. Antibodies (anti-Ro [SS-A], anti-La [SS-B], rheumatoid factor, antinuclear antibody) were measured. RESULTS: 341 subjects were examined. Twenty four per cent had dry eye symptoms, 29% dry mouth symptoms, and 14% both. There was only a weak association between the presence of oral or ocular symptoms and their respective test results. Associations were strongest between dry mouth symptoms and positive test results, and in subjects under 55 years of age. There was no association between the presence of autoantibodies and either symptoms or signs of dry eyes or dry mouth. CONCLUSION: Only weak associations were found between self reported symptoms of dry eyes and dry mouth and objective measures said to define Sjögrens syndrome in the general population. The clinical significance of these symptoms in the community needs reappraisal.